2015
DOI: 10.1111/bcp.12676
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of PF‐05231023, a novel long‐acting FGF21 mimetic, in a first‐in‐human study

Abstract: AIMSThe aim of the present study was to evaluate the pharmacokinetics/pharmacodynamics (PK/PD), safety and tolerability of single intravenous (IV) doses of PF-05231023, a long acting fibroblast growth factor 21 (FGF21) analogue being developed for the treatment of type 2 diabetes mellitus (T2DM). METHODST2DM subjects (glycosylated haemoglobin: 7.0-10.5%; on stable metformin therapy and/or diet and exercise) were randomized to receive a single dose of placebo or PF-05231023 (0.5-200 mg). Safety evaluations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 23 publications
7
63
0
Order By: Relevance
“…PEGylated FGF21 [134,135], FGF21-antibody conjugates [136], and antibody-based activation of the FGFR/β-Klotho complex [137] are under study. Also, the FGF21 analogs LY2405319 and PF05231023 were tested in two different pilot studies in humans [138,139]. LY2405319 was administered subcutaneously once daily for 4 weeks in patients with diabetes and obesity.…”
Section: Fgf21 To Combat Obesity In Humansmentioning
confidence: 99%
“…PEGylated FGF21 [134,135], FGF21-antibody conjugates [136], and antibody-based activation of the FGFR/β-Klotho complex [137] are under study. Also, the FGF21 analogs LY2405319 and PF05231023 were tested in two different pilot studies in humans [138,139]. LY2405319 was administered subcutaneously once daily for 4 weeks in patients with diabetes and obesity.…”
Section: Fgf21 To Combat Obesity In Humansmentioning
confidence: 99%
“…Only two FGF21 analog are study in humans [22,23] as been performed and the results of these studies shown a decrease of body weight, decrease of insulin resistance, decrease of triglycerides, and LDL cholesterol with increase of HDL.…”
Section: Fgf21 Metabolism and Lipodystrophymentioning
confidence: 99%
“…The metabolic action of FGF21 appears to be conserved in obese diabetic humans, at least to a certain extent. Small clinical trials have demonstrated that FGF21 analogs are efficacious in inducing weight loss and correcting hyperinsulinemia, dyslipidemia, and hypoadiponectinemia in obese individuals with type 2 diabetes (15,16).…”
mentioning
confidence: 99%